Reduced glucocerebrosidase activity in monocytes from patients with Parkinson's disease. Issue 1 (December 2018) - Atashrazm, Farzaneh; Hammond, Deborah; Perera, Gayathri; Dobson-Stone, Carol; Mueller, Nicole; Pickford, Russell; Kim, Woojin; Kwok, John; Lewis, Simon; Halliday, Glenda; Dzamko, Nicolas
Abstract Missense mutations in glucocerebrosidase (GBA1 ) that impair the activity of the encoded lysosomal lipid metabolism enzyme (GCase) are linked to an increased risk of Parkinson's disease. However, reduced GCase activity is also found in brain tissue from Parkinson's disease patients withoutGBA1 mutations, implicating GCase dysfunction in the more common idiopathic form of Parkinson's disease. GCase is very highly expressed in monocytes, and thus we measured GCase activity in blood samples from recently diagnosed Parkinson's disease patients. Flow cytometry and immunoblotting assays were used to measure levels of GCase activity and protein in monocytes and lymphocytes from patients with Parkinson's disease (n = 48) and matched controls (n = 44). Gene sequencing was performed to screen participants forGBA1 missense mutations. In the Parkinson's disease patients, GCase activity was significantly reduced in monocytes, but not lymphocytes, compared to controls, even whenGBA1 mutation carriers were excluded. Monocyte GCase activity correlated with plasma ceramide levels in the Parkinson's disease patients. Our results add to evidence for GCase dysfunction in idiopathic Parkinson's disease and warrant further work to determine if monocyte GCase activity associates with Parkinson's disease progression.